(untitled) (Global Journal of Science Frontier Research, 2012)
Mineral supplements differ in their bio-availability, which must be taken into consideration, before the use of any such supplement. Two crossbred fistulated calves housed in individual pens and fed Calcium carbonate (T1) and Calcite powder (T2) were used to study the distribution and disappearance pattern of calcium and its influence on rumen fermentation. The proportion of Ca distributed in soluble, particulate and solid phase of the rumen digesta, pH of the filtrate, Ammonia-N and VFA concentration, rate of disappearance of Ca and rumen flow rate, dry matter intake and other related measurements were used as evaluation parameters. The results obtained showed that there were no significant difference (P